Tobacco cultivation, food production, and nutrition among smallholders in Malawi - Peters, Pauline E.; Herrera, M. Guillermo (International Food Policy Research Institute, 1994)
Malawi is one of the poorest countries in Sub-Saharan Africa, with a per capita income of about US$170 (World Bank 1990). Although Malawi has an enviable record in achieving national food self-sufficiency, it has achieved that at a very low level of the supply-demand balance; the aggregate picture masks widespread food insecurity at the household level. National statistics indicate that over half of the children under five years of age suffer from malnutrition and almost one in five dies before reaching the age of five. The causes of this grim situation are low incomes, chronic and seasonal food shortages, inadequate diet (especially for weaning infants and children between one and two years of age), and high morbidity rates. To date, policy reforms have included restructuring the Agricultural Development and Marketing Corporation (ADMARC), which is the government marketing agency, and agricultural pricing policies. Smallholder response to higher producer prices has increased sales to ADMARC, but this seems to indicate switches among crops rather than an aggregate increase in output (Lele 1989b). This study was conducted in 1986-87 to assess the impact of the commercialization of maize and tobacco in an area in southern Malawi